Cucullanus marajoara n. sp. (Nematoda: Cucullanidae), a parasite of Colomesus psittacus (Osteichthyes: Tetraodontiformes) in the Marajó, Brazil - Pinheiro,Raul Henrique da Silva (2018)
Abstract Cucullanus marajoara n. sp. (Cucullanidae) is reported to parasitize Colomesus psittacus (Tetraodontiformes), which is a fish species from the Marajó Archipelago, state of Pará, estuarine region of the Brazilian Amazon. The new species differs from similar species by the presence of a protruding upper lip on the cloacal opening, the distribution of the cloacal papillae: five pre-cloacal papillae pairs and 5 are ventral and located posteriorly to the pre-cloacal sucker and an unpaired papilla is located on the upper cloacal lip and five post-cloacal pairs, and a pair of lateral phasmids located between papillae pairs. Additionally, Cucullanus marajoara n. sp. is compared to other species of this genus described in Brazil, particularly Cucullanus ageneiosus and Cucullanus oswaldocruzi, which both occur in the same zoogeographic region of this study but parasitize fish of a different order (Siluriformes). Cucullanus dodsworthi and Cucullanus brevicaudatus are the only described species parasitizing fish of the order Tetradontiformes in Brazil, and the new species differs from these species by the distribution of the cloacal papillae and the host habitat. The description of Cucullanus marajoara n. sp. adds data to the biodiversity of described parasites that parasitize Tetradontiformes of the estuarine ichthyofauna in the Brazilian Amazon.